2003
DOI: 10.1002/app.13123
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of polystyrene–montmorillonite nanocomposites by suspension polymerization

Abstract: Organophilic montmorillonite was prepared using ion-exchange method between sodium ions in clay layers and stearyltrimethyl ammonium chloride in the various solvents, including deionized water, ethanol, acetone, and toluene. The montmorillonite has the largest d 001 spacing, as determined by X-ray diffraction in toluene, than the other solvents considered. Ethanol can completely wash out the overexchanged stearyltrimethyl ammonium chloride among layers of montmorillonite. However, deionized water is the prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…They concluded that the modification increased the dispersion of CB in the PS matrix by increasing the compatibility between the modified CB and styrene [23,24] . A similar modification effect was obtained in a PS/MMT nanocomposite [25,26] .…”
Section: Introductionsupporting
confidence: 55%
“…They concluded that the modification increased the dispersion of CB in the PS matrix by increasing the compatibility between the modified CB and styrene [23,24] . A similar modification effect was obtained in a PS/MMT nanocomposite [25,26] .…”
Section: Introductionsupporting
confidence: 55%
“…Changes in the interlayer distance before and after ion-exchange reaction were monitored using XRD and also the distance between clay layers were calculated using the Bragg's law (Eq. 2) [29]. Figure 2 shows X-ray diffraction patterns for pristine and modified clay layers with different DDTMAB and VBTMAC ratios.…”
Section: Resultsmentioning
confidence: 97%
“…This behavior corresponds to exfoliated LS in PSt matrixes. [1][2][3] After our knowledge this synthesis method was not mentioned until now, but there are reports involving emulsion and suspension polymerization, [9,20] miniemulsion [18] or mass polymerization. [22] Monomer insertion in the interlayer spaces of MMT creates the premises for LS exfoliation.…”
Section: Resultsmentioning
confidence: 99%
“…[9,20] These systems are assuming latex nanoparticles which are containing dispersed fillers (LS) also to nanoscale that is a particulate class of materials for a real scientific and applicative interest. [1][2][3]7] 2.…”
Section: Introductionmentioning
confidence: 99%